Pengaruh Kualitas Pelayanan, Kualitas Produk dan Citra Merek terhadap Keputusan Pembelian VAPE STORE (GHOST VAPE) - Bintang Adriansyah; Verry Cyasmoro (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The purpose of this study is to analyze the influence of “service quality, product quality, and brand image on purchasing decisions.” This study is motivated by increasingly fierce business competition, which places demands on companies to better understand the various factors that influence consumer purchasing decisions. Good service quality, product quality that meets consumer expectations, and a positive brand image are believed to increase trust and encourage consumers to make purchases. Therefore, companies need to focus on these three factors to maintain competitiveness and increase sales. This study uses a quantitative approach with a survey method. The sampling technique used was accidental sampling, involving 165 respondents who are consumers of the research object. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with the help of SPSS software (version 25). Data analysis includes validity tests, reliability tests, classical assumption tests, partial tests (t-tests), simultaneous tests (F-tests), and coefficients of determination (R²). The results show that service quality, product quality, and brand image have a positive and significant influence on purchasing decisions, both partially and simultaneously. Service quality is the variable with the most dominant influence compared to other variables. These findings indicate that improving service quality, providing high-quality products, and strengthening brand image can lead to increased consumer purchasing decisions. The results of this study are expected to serve as a consideration for companies in formulating marketing strategies and increasing customer satisfaction and loyalty.